Approaches to Middle Stone Age landscape archaeology in tropical Africa. (January 2017) - Wright, David K.; Thompson, Jessica C.; Schilt, Flora; Cohen, Andrew S.; Choi, Jeong-Heon; Mercader, Julio; Nightingale, Sheila; Miller, Christopher E.; Mentzer, Susan M.; Walde, Dale; Welling, Menno; Gomani-Chindebvu, Elizabeth
Abstract: The Southern Montane Forest-Grassland mosaic ecosystem in the humid subtropics southern Rift Valley of Africa comprised the environmental context for a large area in which modern human evolution and dispersal occurred. Variable climatic conditions during the Late Pleistocene have ranged between humid and hyperarid, changing the character of the ecosystem and transforming it at different points in time into a barrier, a refuge, and a corridor between southern and eastern African populations. Alluvial fans presently blanket the areas adjacent to major river systems, which were key areas of prehistoric human habitation. These sets of variables have created conditions that are both challenging and advantageous to conduct archaeological research. Lateritic soil development has resulted in poor organic preservation and facilitated insect bioturbation, which has demanded an integrated micro-macro scale approach to building a reliable geochronology. An integrated field and analytical methodology has also been employed to identify the nature and degree of post-depositional movement in alluvial deposits, which preserve a wide range of spatial integrity levels in buried stone artifact assemblages between 47 and 30 ka in Karonga, northern Malawi. This paper describes the methodological advances taken toward understanding open-air Middle Stone Age archaeology in sub-tropical Africa, and explores the inferential potential for understanding Pleistocene human ecology in the important southern Rift Valley region. Highlights: Interpreting MSA sequences from open-air sites is challenging in tropical environments. We advocate using sedimentology, micromorphology, OSL and phytolith analyses to analyze site taphonomy. Lake proxy data, phytoliths and micromorphology show variable mildly xeric to pluvial ecosystems. Chaminade-II has MSA activity from >47 to >17ka on a slowly aggraded, partially eroded alluvial fan. Post-depositional effects must be considered to accurately reconstruct site histories.